Estudo do mecanismo catalítico da enzima pirofosforilase do fungo moniliophthora perniciosa por de métodos QM/MM - Teles, André Lacerda Braga (2011)
In 1989, the brazillian cocoa yeld suffered a breakdown, wich can be explained, in part, by the rise and development of the Moniliophthora perniciosa fungus, wich is responsible for a plague known by witch’s broom. This plague affects the cocoa harvests leading to significant social and economic damages. In a search for the effective control of witch’s broom, the metabolic chitin synthesis route was analysed in the search of a potential biological target to prevent its synthesis. Chitin is the main component of the fungus celular wall. The selected target on the metabolic route is the pyrophosphorylase enzyme, wich is responsible for catalyzing the reaction that forms UDP-N-acetylglucosamine-1-phosphate, one of the intermediates of the chitin synthesis route. Thus, the inhibition of this enzime will affect the chitin production and, as a consequence, the celular wall synthesis, vital to the fungi life. In the present work, realized by means of computational chemistry methods, the enzymatic reaction mechanism to the UDP-N-acetylglucosamine formation were studied. Molecular Dynamics and Quantum Mechanics/Molecular Mechanics (QM/MM) methods were used to develop the studies. The reaction mechanism assumed was a type 2 nucleophilic substitution (NS2). A transition structure with a pentavalent phosphorus atom was elucidated, this structure realizes interactions at the catalytic site with the residues Gly-112, 113, Arg-116, Lys-123 e Gly-225. This interaction must be explored for the rational design of new inhibitors candidates to the referred enzyme. A scan of the reaction with addition of a divalent metal Mg+2 was also carried, the location of the metal insertion point in the system was obtained regarding the literature. This simulation produced a phosphate intermediate structure with a dissociative character, the scan showed no reduction in the activations energy of the reaction. As explanatory hypothesis it was suggested that the local described in the literature may be incorrect for the metal location point or, in a last analysis, a mechanism of catalysis that, in the presence of magnesium cation, do not have a SN2 path as the main mechanism.